HIV and aging - Lee, Sharon Dian (Informa Healthcare, 2008)
"More than two decades into the global HIV epidemic, many HIV positive patients who have access to antiretroviral medications are graying. These patients and their clinicians now face another set of complex health issues related to aging. HIV and Aging examines the known effects of HIV and HIV medications on older patients and on their immune systems. The book explores the coalescence of aging and HIV on neurologic, psychiatric, cardiovascular, endocrine, renal, and pulmonary systems and oncology."--Jacket.